2006
DOI: 10.1007/s10593-006-0191-2
|View full text |Cite
|
Sign up to set email alerts
|

Unusual reaction of cyanoacetic acid esters with sym-triazine monoazides

Abstract: Continuing our studies on synthesis of derivatives in the sym-triazine series based on 2-azido-4,6-disubstituted 1,35-triazines [1-3] by reactions of compounds 1a-d with methyl cyanoacetate and ethyl cyanoacetate, we obtained derivatives of a novel coupled heterocyclic system: 2-[1,3,5]triazin-2-yl-1,2-dihydro[1,2,3,4]tetrazine-5-carboxylic acid esters 2a-d. a R 1 = NH 2 , R 2 = NEt 2 ; b R 1 = R 2 = NMe 2 ; c R 1 = PhNMe, R 2 = NMe 2 ; d R 1 = NH 2 , R 2 = piperidino; a, b R 3 = Me, c, d R 3 = EtThe IR spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Compounds 3d, 3g, 4b, and 5a-c displayed the maximum intensity of the molecular ions. The fragmentation patterns of the molecular ions under electron impact were found to be the same as it was observed for the earlier synthesized heterocyclic derivatives of the 1,3,5-triazine [8,11,25].…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Compounds 3d, 3g, 4b, and 5a-c displayed the maximum intensity of the molecular ions. The fragmentation patterns of the molecular ions under electron impact were found to be the same as it was observed for the earlier synthesized heterocyclic derivatives of the 1,3,5-triazine [8,11,25].…”
Section: Resultssupporting
confidence: 77%
“…Previously, we reported that using esters of cyanoacetic acid as a methylene active reagent in reaction with 2-azide-4,6-disubstituted-1,3,5-triazines lead to the formation of sixmembered 1,2,3-triazinyl-1,2,3,4-tetrazines [11]. It was interesting to compare different reaction conditions for the similar reaction of azido-derivatives of 1,3,5-triazine with less reactive cyanoacetamide (CAA) as a reagent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds IIIc and IVc have the maximum intensity of the molecular ions. The fragmentation pattern of the molecular ions under electronic impact is the same as has been observed for the synthesized heterocyclic derivatives of the 1,3,5-triazine [36,37,[40][41][42][43].…”
Section: Resultsmentioning
confidence: 58%
“…Furthermore, 1,3,5-triazine derivatives posses a wide variety of biological activity as HIV treatment, and as catalysts, herbicides, carcenolytics [17][18][19][20], as well as compounds with growth-stimulating activity, antidote activity, nontoxic cationic surfactants, and inhibitors of the oil oxidizing processes [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%